3rd IEEE International Symposium on Biomedical Imaging: Macro to Nano, 2006.
DOI: 10.1109/isbi.2006.1625130
|View full text |Cite
|
Sign up to set email alerts
|

Shape Analysis Using the Fisher-Rao Riemannian Metric: Unifying Shape Representation and Deformation

Abstract: We show that the Fisher-Rao Riemannian metric is a natural, intrinsic tool for computing shape geodesics. When a parameterized probability density function is used to represent a landmark-based shape, the modes of deformation are automatically established through the Fisher information of the density. Consequently, given two shapes parameterized by the same density model, the geodesic distance between them under the action of the Fisher-Rao metric is a convenient shape distance measure. It has the advantage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…The geodesic and the corresponding geodesic distance seem to be a natural thing to study and has, for example, found applications in image analysis (see [19,20], for example).…”
Section: Applicationsmentioning
confidence: 99%
“…The geodesic and the corresponding geodesic distance seem to be a natural thing to study and has, for example, found applications in image analysis (see [19,20], for example).…”
Section: Applicationsmentioning
confidence: 99%
“…In order to compare them in a manner that is invariant to their parameterizations, one forms a quotient space, called the shape space, that is defined as the space of closed curves modulo all possible re-parameterizations [7]. A related problem is to perform non-rigid registration of points across curves [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This task is accomplished by imposing Riemannian structures on appropriate manifolds formed by these functions. The most natural Riemannian metric in this context is the so-called Fisher-Rao metric, which has been used extensively in computer vision [6,5,10,11].Čencov [2] showed that this is the only metric that is invariant to re-parametrizations of those functions. This metric has also played an important role in information geometry due to the pioneering efforts of Amari [1].…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting approach proposes an entropy based criterion to find shape correspondences, but requires implicit surface representations (10). Other works combine the search for correspondences with shape based classification (11,12) or with shape analysis (13), however, these methods are not easily adaptable to multiple observations of unstructured point sets. The approach in (14) for unstructured point sets focuses only on the mean shape.…”
Section: Introductionmentioning
confidence: 99%